Green synthesis of silver nanoparticles (AgNPs) incorporated with Adenia trilobata leaf extracts and its anti-bacterial application - Md. Johurul Islam; Kamaruzzaman; Md. Forhad Hossain; Md. Abdul Awal; Md. Rezwanur Rahman; M. M. Alam (AIP Advances, 2022)
Currently, eco-friendly, cost-effective, and simple synthesis techniques are drawing the attention of nanoparticle researchers. The conversion of silver ions to silver nanoparticles (AgNPs) is carried out using the Adenia trilobata leaf extract, which is capable of acting as an exclusive reducing agent. AgNPs show very crucial antibacterial properties and are nontoxic for humans. The color of the solution changes from light blue to brown, ensuring the formation on nanoparticles. The biosynthesized AgNPs are incorporated into cotton fiber, and their antibacterial activity on gram negative (E. coli) bacteria has been studied. The UV/Vis and absorption spectroscopy analysis shows a surface plasmon resonance peak at 445 nm. The x-ray diffraction measurement reveals peaks at 38.02 and 44.23, and the average particle size is 18.30 nm. Field emission scanning electron microscopy has been performed to find the size, shape, and morphology of the treated nanoparticles and the AgNP-incorporated cotton fiber. The Fourier transform infrared spectroscopy result shows the presence of functional groups of AgNPs and capping agents. The antibacterial activity on gram negative (E. coli) bacterial strains for the both cases showed a promising result.